Ewolucja prawa własności w Polsce Ludowej w latach 1944–1956 - Bużowicz, Mateusz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The article presents the process of the evolution of property rights in the Polish People’s Republic during the years 1944–1956. It commences by laying out various stages of property rights evolution during the initial period of the Polish People’s Republic and, subsequently, recounts the attitude of contemporary authorities towards property rights – starting in 1944, when the communist government began the process of consolidating the communist system and property rights were perceived in abstract terms. In the following part of the article, the relationship between the constitution of the Polish People’s Republic and property rights is analyzed, and the author argues that, in fact, the constitution marks the first time property rights were divided into three categories, namely: public, individual, and personal. The article concludes by emphasizing the breakthrough role of year 1956 in shaping the attitude of the communist authorities toward property rights
Keywords: prawo własności; Polska Ludowa; dekret PKWN